ANALISIS JENIS DAN KONSENTRASI ENZIM TERHADAP DAYA SIMPAN VCO (VIRGIN COCONUT OIL) - M FM Fuad (AGROINTEK, 2012)
Oil products susceptible to damage. Several causes of oil damages is water, light, heat, oxygen, metals, acids, alkalis, and enzymes. This study aimed to obtain information about effect of several types of enzymes, namely crude extract of papain enzyme (from papaya), bromelain enzyme (from pineapple) and zingibain enzyme (from ginger) to the yield and shelf life of the virgin coconut oil was produced. The design of experiments in this study were split plot design with two plots were 3 (three) levels of enzyme type as a main plot and 3 levels of enzyme concentration as a sub plot. Virgin coconut oil stored and tested % FFA content gradually to determine shelf life. Estimation of deterioration rate by using the Arrhenius equation. Shelf life determination based on % FFA of the virgin coconut oil. The results show that shelf life of VCOwith the shortest shelf life wasVCO produced by the papain enzyme, bromelain enzyme, and the longest wasVCO produced by zingibain enzyme, respectively.